The Dynamics of Pretend Play Development in Early Childhood - Brėdikytė, Milda; Brandišauskienė, Agnė; Sujetaitė - Volungevičienė, Giedrė (Pedagogika, 2015)
The phenomenon of play is constantly raising many questions for researchers and practitioners. Why play important, what kind of play is should be promoted in kindergarten classrooms, should it be supported and how? This article provides a short analysis on the concept of play and introduces an investigation aimed at analyzing the dynamics of the development of children’s pretend play in early childhood settings. This research is performed within the framework of Cultural-Historical theory of play. The development of children’s pretend play in ECEC groups will be discussed; gender differences and the level of pretend play within different age groups of children will be analyzed.